Relationship between young learners’ learning styles and development of writing skills using PowerPoint as a teaching aid - Mat Daud, Nuraihan (2011)
This paper discusses the correlation between young learners’ writing performance and their learning styles when PowerPoint was used in teaching writing skills. This study focuses on the sensory learning styles which comprises visual, auditory, kinesthetic and tactile learning styles (perceptual learning style). A longitudinal study was first conducted followed by a quasi-experiment in a Malaysian primary school. Participants’ learning styles were measured and writing performance assessed. The analysis of results shows that students with various learning styles performed better when PowerPoint was used in the teaching of writing. However, the increase was not statistically significant.